Determinants of Reading Interest with User Satisfaction as a Mediator at the National Library of the Republic of Indonesia - Bunga, Yuliatry; Herawati, Aty (Dinasti Publisher, 2024)
The National Library of the Republic of Indonesia is a non-ministerial government institution that carries out government duties in the library sector which functions as a supervisory library, reference library, deposit library, research library, preservation library and library network center and is located in the nation's capital. As a library institution, the National Library of the Republic of Indonesia must strive to increase the number of visits and reading interest of the Indonesian people.. The aim of this research is to analyze reading interest at the National Library of the Republic of Indonesia and user satisfaction as a mediator variable. The variables used as factors influencing reading interest in this research are promotion and visits. The research was conducted by surveying 100 visiting users using convenience sampling techniques. Data analysis was carried out using path analysis. The results of the research are that there is an influence of promotion and visits on user satisfaction and user satisfaction has an influence on reading interest. User satisfaction is a mediating variable, meaning that reading interest is influenced by promotion both directly and indirectly through user satisfaction and reading interest is influenced by visits both directly and indirectly through user satisfaction.